A treatise on the art of reading by the scholar Abd al-Rahman bin Ahmad Adud al-Din al-Aji (d.: 756 AH), study and investigation (Journal of the College of Basic Education, 2022)
Praise be to God, who created and fashioned, and who destined and guided, and prayers and peace be upon the master of creation, the imam of truth, our master Muhammad, and his family and companions, and peace be upon them all. As for after:Reading is one of the purely Arabic sciences. Our first scholars were concerned with it a lot and devoted a lot of writings and letters to it explaining and clarifying this science from Arabic.And "Risala fi Fann al-Tara'ah" by Judge Abd al-Rahman al-Ayji is the best proof of that.The correctness in their writings and messages through the warnings, commandments, and observations contained in this great message and as a contribution from me, I chose this great manuscript to achieve it and bring it to light, and the research required me to put a plan for it, so I divided it into an introduction and two chapters, as follows:The first chapter: a study on the author and the message and includes eight topics:The first topic: his name, lineage, and lineage.The second topic: his birth and upbringing.The third topic: his sheikhs, his students, and his writings.The fourth topic: his scientific standing, and the scholars' praise of him.The fifth topic: his death.The sixth topic: method and resourcesThe seventh topic: the importance of the message and its relationship to teaching methodsThe eighth topic: description of the manuscript. Investigative approachChapter two: the text investigated.Finally, I ask God to make my work pure for His face, to grant the researchers and investigators success in reviving the heritage of our Islamic nation, and to forgive me for slipping in my work.